Absence of common grammar and contemporary emotional political praxis in Chile - Arqueros, Claudio (2024)
This article aims to explore the intellectual foundations behind the contemporary Chilean political landscape in the context of the October 2019 revolt. We will understand the absence of a common grammar as the lack of universalist modern philosophical principles that allow maintaining an environment of dialogue and democratic collaboration in contemporary politics. This absence is due, as we will show, to the conscious affirmation of an understanding of postmodern intellectual principles —relativism, non-truth, molecularity— and their practical application in political work. The figure of feminist emotive subjectivities in the context of the digital age and their molecular emergence will be highlighted as a challenge to understanding the insurgencies that have occurred in Chile and the world in recent years.